The impact of tumor budding and single-cell invasion on survival in patients with stage III/IV locally advanced oral squamous cell carcinoma- results from a prospective cohort study - Hakim, Samer G.; Alsharif, Ubai; Falougy, Mohamed; Tharun, Lars; Rades, Dirk; Jensen, Justus (Frontiers in Oncology, 2024)
Introduction Tumor budding (TB) refers to the presence of small clusters of tumor cells at the invasive front of a malignant tumor. Single tumor cell invasion (SCI) is an extreme variant of TB, in which individual loose tumor cells are present at the invasive front. Both TB and SCI are important histomorphologic risk factors postulated to indicate loss of cellular cohesion. In this study, we investigated the influence of TB and SCI on different survival outcomes in patients with locally advanced oral squamous cell carcinoma (OSCC). Methods We included 129 patients with locally advanced OSCC (pT3-4) from a single-center, prospectively maintained cohort. We examined the association of TB and SCI with the presence of occult lymph node metastasis using a logistic regression model. Survival probabilities were estimated using the Kaplan-Meier method and cumulative incidence functions. The association of TB and SCI on overall survival (OS), oral cancer-specific survival (OCSS), and local recurrence-free survival (LRFS) was investigated using Cox’s proportional hazards regression models. Results TB was detected in 98 (76%) of the tumors, while SCI was observed in 66 (51%) patients. There was a significant association between TB and the occurrence of occult lymph node metastasis (OR=3.33, CI: 1.21-10.0). On multivariate analysis, TB had no detectable impact on survival outcomes. However, SCI showed a higher risk for local recurrence (Hazards ratio (HR): 3.33, CI: 1.19 – 9.27). Discussion This study demonstrates that TB and SCI in locally advanced OSCC function as an independent risk factor for occult lymph node metastases, as well as local recurrences. Both histomorphologic risk factors could serve as an additional parameter for stratifying therapy and escalating multimodal treatment approaches.